Screening and Comparision of Antibacterial Activity of Indian Spices - C. Ramalingam*, Madhumita Rakshit and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Spices have been shown to possess medicinal values, particularly antimicrobial property. This study compares the sensitivity of some human and food borne pathogenic bacteria to various spice extracts. Of the different spices tested only Garlic, Turmeric, Fenugreek, Cardamom, Star anise, Red chilly, Coriander and Clove were found to possess broad spectrum antimicrobial activity. When exposed to higher temperature, turmeric looses the antimicrobial property. But at higher temperature, the antimicrobial activity of Clove and Ajowain increases. Thus spices might have a great potential to be used as antimicrobial agents at different food products processed at different temperature.